1995
DOI: 10.1111/j.1600-051x.1995.tb01788.x
|View full text |Cite
|
Sign up to set email alerts
|

The subgingival microflora and gingival crevicular fluid cytokines in refractory periodontitis

Abstract: Refractory periodontitis manifests as a rapid, unrelenting, progressive loss of attachment despite the type and frequency of therapy. This study examined possible relationships between cytokine levels in gingival crevicular fluid (GCF), occurrence of specific periodontopathic microflora, and disease activity in patients with refractory periodontitis. Refractory periodontitis patients (7 male and 3 female) were selected on the basis of history and longitudinal clinical observations. In each patient, 2 teeth wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
125
2
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(138 citation statements)
references
References 25 publications
7
125
2
4
Order By: Relevance
“…This discrepancy may result from the use of different sampling methods and/or ELISA kits. GCF IL-1β concentrations were almost 2-fold higher (p<0.05) in our PD patients than in the healthy controls, consistent with reports of a strong relationship between IL-1β and periodontal inflammation (26,(28)(29)(30)(31). Masada et al (32), in a study of 15 patients with moderate-to-severe PD, found that their elevated GCF IL-1α and IL-1β concentrations were reduced with periodontal treatment.…”
Section: Discussionsupporting
confidence: 89%
“…This discrepancy may result from the use of different sampling methods and/or ELISA kits. GCF IL-1β concentrations were almost 2-fold higher (p<0.05) in our PD patients than in the healthy controls, consistent with reports of a strong relationship between IL-1β and periodontal inflammation (26,(28)(29)(30)(31). Masada et al (32), in a study of 15 patients with moderate-to-severe PD, found that their elevated GCF IL-1α and IL-1β concentrations were reduced with periodontal treatment.…”
Section: Discussionsupporting
confidence: 89%
“…High amounts of IL-6 were detected in patients with periodontitis (21,22), in active sites of refractory periodontitis (23), as well as in sites undergoing orthodontic movement, emphasizing the important role of IL-6 in the bone remodeling process (24). IL-6 was observed to correlate with the severity of periodontal disease (25), which may indicate that IL-6 could be a diagnostic marker for sites of active periodontal disease (26).…”
Section: Discussionmentioning
confidence: 94%
“…Reinhardt y cols 27 encontraron niveles significativamente mayores en FGC de IL-6 en localizaciones de pacientes con periodontitis refractaria que en sujetos estables. Lee y cols 28 encontraron niveles significativamente mayores de IL-6 en FGC en localizaciones activas que inactivas, tanto en baseline como a los 3 meses. Geivelis y cols 29 observaron una correlación positiva entre sangrado gingival e IL-6, y entre profundidad de sondaje e IL-6 en pacientes con periodontitis.…”
Section: Palabrasunclassified